Development and Optimization of a GMP-Compliant Manufacturing Process for a Personalized Tumor Lysate Dendritic Cell Vaccine - Boudousquié, Caroline (Vaccines (Basel), 2020)
With the emergence of immune checkpoint inhibitors and adoptive T-cell therapies, there is a considerable interest in using personalized autologous dendritic cell (DC) vaccines in combination with T cell-targeting immunotherapies to potentially maximize the therapeutic impact of DC vaccines. Here, we describe the development and optimization of a Good Manufacturing Practice (GMP)-compliant manufacturing process based on tumor lysate as a tumor antigen source for the production of an oxidized tumor cell lysate loaded DC (OC-DC) vaccine. The manufacturing process required one day for lysate preparation and six days for OC-DC vaccine production. Tumor lysate production was standardized based on an optimal tumor digestion protocol and the immunogenicity was improved through oxidation using hypochloric acid prior to freeze-thaw cycles resulting in the oxidized tumor cell lysate (OC-L). Next, monocytes were selected using the CliniMACS prodigy closed system and were placed in culture in cell factories in the presence of IL-4 and GM-CSF. Immature DCs were loaded with OC-L and matured using MPLA-IFNγ. After assessing the functionality of the OC-DC cells (IL12p70 secretion and COSTIM assay), the OC-DC vaccine was cryopreserved in multiple doses for single use. Finally, the stability of the formulated doses was tested and validated. We believe this GMP-compliant DC vaccine manufacturing process will facilitate access of patients to personalized DC vaccines, and allow for multi-center clinical trials.